2016
DOI: 10.1016/j.agwat.2015.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Chinese rose ( Rosa chinensis ) growth and ion accumulation under irrigation with waters of different salt contents

Abstract: a b s t r a c tSoil salinity and saline groundwater are major constraints to the cultivation of landscape plants in coastal regions. Soil tillage, drip-irrigation and a gravel-sand layer were used for reclamation of high saline siltsoils in a coastal region of China. Chinese roses (Rosa chinensis), a salt-sensitive species, were planted in the reclaimed soil under field conditions to determine the effects of salinity on rose growth and ion uptake, using five salinity levels of 0.8, 3.1, 4.7, 6.3 and 7.8 dS/m o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 44 publications
4
21
0
Order By: Relevance
“…The similar result was also found by Fernández-García et al (2014) and Glaeser et al (2016). However, Li et al (2016) didn't find the significant change in root/shoot ration for R. chinensis, which may be controlled by the genes in plants (Coyle and Coleman, 2005).…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The similar result was also found by Fernández-García et al (2014) and Glaeser et al (2016). However, Li et al (2016) didn't find the significant change in root/shoot ration for R. chinensis, which may be controlled by the genes in plants (Coyle and Coleman, 2005).…”
Section: Discussionsupporting
confidence: 75%
“…R. pseudoacacia seedlings decreased TRL and TRSA, which suggested that the ability of ion and water uptake decreased (Wang et al, 2006). The decrease of total root length was also found in Euonymus plants (Gómez-Bellot et al, 2013), Callistemon citrinus (Álvarez and Sánchez-Blanco, 2014) and R. chinensis (Li et al, 2016). NRT decreased in saline conditions in this study, which indicated that the production of new roots was hampered.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations